WORD ORDER AS A TRANSLATION CHALLENGE FROM HUNGARIAN INTO SLAVIC LANGUAGES: A CONTRASTIVE AND TRANSLATION-ORIENTED STUDY - Берта, Елеонора (SWorldJournal, 2026)
The present study examines the major translation difficulties arising from the specific word order characteristics of Hungarian when translated into Slavic languages, with particular reference to Ukrainian. Although both Hungarian and Slavic languages all